Effect of sugar and acid composition, aroma release and assessment conditions on aroma enhancement by taste in model wines - Arvisenet, Gaëlle; Ballester, Jordi; Ayed, Charfedinne; Sémon, Etienne; Andriot, Isabelle; Le Quere, Jean-Luc; Guichard, Elisabeth (Elsevier, 2018)
Context: When congruent taste and retronasal aroma are perceived simultaneously, aroma can be enhanced by taste. Different explanations have been proposed: (i) physico-chemical interactions between tastants and aroma compounds, inducing a change of the aroma stimulus before it reaches the receptors, (ii) a contextual bias during sensory tests (dumping), when at least one relevant attribute is not proposed to the panelists to assess a product, (iii) a misunderstanding of the conceptual difference between aroma and taste, or (iv) a perceptual incapability of panelists to distinguish between two congruent percepts. This study was undertaken to better understand aroma enhancement by taste in model wines containing different sugar and acid concentrations but the same volatile composition. Method: We used a twofold approach: model wine retronasal aroma intensity was assessed twice by trained panelists. During the first session, panelists only assessed aroma intensity. During the second session, taste intensity was assessed before aroma intensity, to reduce dumping effects. In-mouth release of volatile compounds was measured by nosespace analysis with the same panelists. Results: Acid concentration influenced aroma compounds release, but it did not impact perceived aroma intensity. Increasing sugar concentration delayed ethyl octanoate (EO) release after swallowing. When taste was not assessed, perceived aroma intensity was not explained by aroma compounds release, but it increased with sugar concentration, probably because of a dumping effect. When taste was assessed, aroma intensity also depended on sugar concentration, but it was significantly correlated to the time of release of EO. Our hypothesis is that when taste declined, late aroma was more easily individualized, and thus assessed with a higher intensity. This entails that panelists focused on aroma to individualize it from taste. We concluded that trained panelists understand the conceptual difference between taste and aroma, but are not completely able to distinguish congruent and simultaneous taste and aroma percepts.